Memristive behavior of Ti02 thin film by RF magnetron sputtering / Mohammad Mukhlis Ramly - Ramly, Mohammad Mukhlis (2012)
This project is on the fabrication and electrical characteristic of a memristive device with titanium dioxide (Ti02) as an active layer on two different substrates which are silicon (Si) and glass. Bottom electrodes of 60nm thick platinum were grown on the substrates before the TiC>2 deposition. Two layers of TiC>2 thin films were grown on the bottom electrode by radio frequency (RF) magnetron sputtering forming a memristive device. The first set of sample is a layer of T1O2 deposited on silicon substrate and exposed to plasma before the deposition of the second layer. The plasma treatment time was varied; for 0 minutes, 5 minutes and 10 minutes. The second set of sample is a Ti02 layer deposited on glass substrates and being etched by 1% hydrofluoric (HF) before deposition the second layer. The etching time was varied; for 5 seconds and 7 seconds. Current-voltage (I-V) curves of the samples were taken from the voltage loop ranging 0V to -5V, -5V to 5V then back to 0V and also from - 5V to 5V then back to -5V to show the bias dependent switching characteristics that match the electrical behavior reported for memristor. The second set of sample (etching method) gives better memristive behavior compared to the first set of sample (plasma treatment method). Beside, second loops which were measured from -5V to 5V then back to -5V, gives batter memristive behavior with less noise compared to the first loop.